A UML profile for knowledge-based systems modelling - Abdullah, Mohd Syazwan; Paige, Richard; Kimble, Chris; Benest, Ian (2007)
The Knowledge engineering (KE) techniques are essentially based on the knowledge transfer approach, from domain experts directly to systems. However, this has been replaced by the modelling approach which emphasises using conceptual models to model the problem-solving skill of the domain expert.This paper discusses extending the Unified Modelling Language by means of a profile for modelling knowledge-based system in the context of Model Driven Architecture (MDA) framework.The profile is implemented using the eXecutable Modelling Framework (XMF) Mosaic tool.A case study from the health care domain demonstrates the practical use of this profile; with the prototype implemented in Java Expert System Shell (Jess). The paper also discusses the possible mapping of the profile elements to the platform specific model (PSM) of Jess and provides some discussion on the Production Rule Representation (PRR) standardisation work.